Real world community health nursing an interactive CD-ROM - Hale, Patty J.; Mosby, Inc. (St. Louis, Mo. : Mosby, 2005)
(Producer) Features more than 40 interactive exercises that challenge critical thinking skills. Takes user to the Internet to collect data, analyze a real community, and learn the latest on communicable and reportable diseases. Contains crossword puzzles, video clips, photos, and case studies. Provides interactive exercises on community and public health nursing
Title from disc label
System requirements: Pentium or faster processor; 32 MB RAM; Windows 95 or later; 4X or faster CD-ROM drive; SVGA 640 x 480 with thousands of colors
System requirements: Macintosh, PowerPC or faster processor; 32 MB RAM; Mac OS version 7.6.1 or later; 4X or faster CD-ROM drive; SVGA 640 x 480 with thousands of colors
Keywords: Community health nursing; Public Health Nursing